1985
DOI: 10.1364/ao.24.001469
|View full text |Cite
|
Sign up to set email alerts
|

Optical implementation of the Hopfield model

Abstract: Optical implementation of content addressable associative memory based on the Hopfield model for neural networks and on the addition of nonlinear iterative feedback to a vector-matrix multiplier is described. Numerical and experimental results presented show that the approach is capable of introducing accuracy and robustness to optical processing while maintaining the traditional advantages of optics, namely, parallelism and massive interconnection capability. Moreover a potentially useful link between neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
145
0
2

Year Published

1986
1986
2005
2005

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 547 publications
(153 citation statements)
references
References 7 publications
0
145
0
2
Order By: Relevance
“…If q T min is the minimal acceptable diffraction efficiency when f3,, = 1/R, then the number of exposures that can be recorded and detected is Ao/Vmi,, or {1 + [91(a)/c(a)]2}l/2A/2V-2n. Under the assumption that Tlmin 10-4, Ao/ 2 ?lmin has been shown to reach 10 3 in BaTiO 3 . 3 1 Even more promising results have been obtained in photo-organics.…”
Section: E Practical Implicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…If q T min is the minimal acceptable diffraction efficiency when f3,, = 1/R, then the number of exposures that can be recorded and detected is Ao/Vmi,, or {1 + [91(a)/c(a)]2}l/2A/2V-2n. Under the assumption that Tlmin 10-4, Ao/ 2 ?lmin has been shown to reach 10 3 in BaTiO 3 . 3 1 Even more promising results have been obtained in photo-organics.…”
Section: E Practical Implicationsmentioning
confidence: 98%
“…This approach was taken by Mok et al, who recorded more than 1000 expo- At 1-,um resolution, N 1 is 10 4 /cm of aperture. Since the maximum rank is approximately Nl, a 1-cm 3 hologram formed of -10,000 exposures would be nearing its maximum information capacity. Even without taking advantage of complex time constants, the state of the art is not far off this pace.…”
Section: E Practical Implicationsmentioning
confidence: 99%
“…There are many possible ways to use this mode of real-time control of array response, but the most interesting possibility is the use of control signals derived from internal feedback to effectuate epigenetic development of the complete system response. As research in neural networks elegantly demonstrates, 33,34 control by suitably convolved feedback signals affords a mechanism for learning and adaptive behavior. Figure 6 suggests in a highly idealized way some aspects of visual perception which might be well addressed in such a photoneural system.…”
Section: Photoneural Systemsmentioning
confidence: 99%
“…Theoretical calculations have shown that the basic origin of these properties resides in highly chage correlated excited states of the w -electron distribution comprising these structuresX' . Thesog striking properties together with demonstrations of 8 phase conjugate wave generation , optical bistability , and associative memory networks have stimulated considerable growth in research and development activities in centers throughout the world.…”
Section: Introductionmentioning
confidence: 99%